Liar's poker : rising through the wreckage on Wall Street - Lewis, Michael (Michael M.) (W.W. Norton, 2010)
The author recounts his experiences on the lucrative Wall Street bond market of the 1980s, where young traders made millions in a very short time, in a humorous account of greed and epic folly.